2007
DOI: 10.3310/hta11030
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of rapid diagnostic tests for the detection of tuberculosis infection

Abstract: Non-UK purchasers will have to pay a small fee for post and packing. For European countries the cost is £2 per monograph and for the rest of the world £3 per monograph.You can order HTA monographs from our Despatch Agents:-fax (with credit card or official purchase order) -post (with credit card or official purchase order or cheque) -phone during office hours (credit card only).Additionally the HTA website allows you either to pay securely by credit card or to print out your order and then post or fax it. NHS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
367
0
28

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 538 publications
(399 citation statements)
references
References 327 publications
(368 reference statements)
4
367
0
28
Order By: Relevance
“…Performance was in line with generally accepted characteristics of molecular testing for M. tuberculosis: 90-100% sensitivity in microscopy smear-positive sputum specimens and 55-75% among smearnegative cases (Armand et al, 2011, Dinnes et al, 2007, Miller et al, 2011, Steingart et al, 2014. There was no apparent effect of chemical composition of PS-MTM on detection of lower bacillary loads as diagnostic performance among smear-negative cases was adequate.We did not test amplification suppression, but think that the effect, if present, was minimal as we were able to successfully amplify M. tuberculosis at relatively low CFU/ml as well as detect smear negative TB cases in the clinical laboratory evaluation.…”
Section: Discussionsupporting
confidence: 71%
“…Performance was in line with generally accepted characteristics of molecular testing for M. tuberculosis: 90-100% sensitivity in microscopy smear-positive sputum specimens and 55-75% among smearnegative cases (Armand et al, 2011, Dinnes et al, 2007, Miller et al, 2011, Steingart et al, 2014. There was no apparent effect of chemical composition of PS-MTM on detection of lower bacillary loads as diagnostic performance among smear-negative cases was adequate.We did not test amplification suppression, but think that the effect, if present, was minimal as we were able to successfully amplify M. tuberculosis at relatively low CFU/ml as well as detect smear negative TB cases in the clinical laboratory evaluation.…”
Section: Discussionsupporting
confidence: 71%
“…The most notable advantage of NAA tests is their rapid turnaround time, which may have important implications for patient management and TB control (Dinnes et al 2007). Compared with culture-based methods, NAA tests can detect the presence of M. tuberculosis bacteria in a specimen weeks earlier for 80-90% of patients suspected to have PTB, whose TB will be ultimately confirmed by culture (CDC 2009).…”
Section: Discussionmentioning
confidence: 99%
“…NAA tests could have the greatest impact in smear-negative disease, as the lower sensitivity makes ruling out disease more difficult. For smear-negative disease, the appropriate use of NAA tests will depend on the associated degree of clinical suspicion (Dinnes et al 2007, CDC 2009.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ziehl Neelsen acid-fast bacilli (AFB) staining is the most commonly used laboratory method to diagnose TB; however, in extra-pulmonary TB, the sensitivity is too low (10-40%) and culture is more sensitive (50-70%) but time-consuming (Garg 1999, Chandramuki et al 2002, Thwaites et al 2004). Newer diagnostic methods based on nucleic acid amplification tests have been developed, but meta-analysis studies have indicated that despite high specificity, the sensitivity is lower and variable (Pai et al 2003, Dinnes et al 2007. T cell based assays detecting INF-γ production have been reported to be promising; however expense, the requirement of fresh clinical specimens and inadequate laboratory infrastructure limit their use in low-income countries.…”
mentioning
confidence: 99%